2004
DOI: 10.3989/scimar.2004.68n1165
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of trophic pathways between plankton and the North Iberian sardine (<i>Sardina pilchardus</i>) using stable isotopes

Abstract: SUMMARY: Feeding on phyto-and zooplankton by juvenile (< 1 year old) and adult sardines (Sardina pilchardus) was inferred from analyses of natural abundance of stable carbon and nitrogen isotopes in samples from the northwestern Iberian Peninsula (Spain) collected at the beginning of the upwelling season and peak spawning period of sardine. Plankton samples were fractionated through nets of 20, 200, 500, 1000 and 2000 µm mesh-size and the muscle protein of individual sardines was isolated before isotopic deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 49 publications
5
53
0
Order By: Relevance
“…Sardines are primarily filter-feeders, whose diet composition is closely related to plankton availability (Varela et al 1988(Varela et al , 1990. In terms of biovolume, sardine diet is mostly supported by mesozooplankton organisms, which are assimilated more efficiently than phytoplankton (van der Lingen 1998, Bode et al 2004). However, it is numerically dominated by organisms smaller than 200 µm, with large quantities of phytoplankton being consumed (Garrido 2003).…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…Sardines are primarily filter-feeders, whose diet composition is closely related to plankton availability (Varela et al 1988(Varela et al , 1990. In terms of biovolume, sardine diet is mostly supported by mesozooplankton organisms, which are assimilated more efficiently than phytoplankton (van der Lingen 1998, Bode et al 2004). However, it is numerically dominated by organisms smaller than 200 µm, with large quantities of phytoplankton being consumed (Garrido 2003).…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…Ecological models based on trophic web interactions and capable of quantitatively describing the structure and function of exploited marine ecosystems (e.g. Ecopath/Ecosim, see Banaru et al 2012, Coll et al 2006 have described sardine in the northwestern Mediterranean as a key species in the trophic web but, with the exception of data from Lee (1961) used in Banaru et al (2012), these models have used data on the diet of sardine from regions other than the northwestern Mediterranean, such as the eastern Mediterranean (Demirhindi 1961) and the Atlantic coast of Spain (Bode et al 2004, Garrido et al 2008. Moreover, detailing the ontogenetic fractions of key species included in the models (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the most important fish resources throughout its range in the northeastern Atlantic, from the North Sea to the Senegalese coast, including the Mediterranean and the Black Seas. Studies of its feeding dynamics have been conducted on the Atlantic coast of Spain, where the diets of juvenile and adult sardine have been found to consist entirely of plankton (Bode et al 2004, Garrido et al 2007 and where adults are able to perform both filter and particulate feeding. Due to this difference between stages, the adults show a greater fraction of phytoplankton in their stomachs than the juveniles do.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies based on stomach content (Varela et al 1988, Garrido 2003, Cunha et al 2005) and stable isotope analyses (Bode et al , 2004 have shown that sardines have a highly diverse diet, dominated in terms of biovolume by micro-and mesozooplankton prey. High numbers of phytoplankton cells, ABSTRACT: Laboratory experiments were conducted to study the effects of different prey types and concentrations on the feeding behaviour of the Iberian sardine Sardina pilchardus.…”
Section: Introductionmentioning
confidence: 99%